The Influence of Mathematics Attitude on Academic Achievement: Intermediary Role of Mathematics Learning Engagement - Zhang Lijie; Mo Zongzhao; Zhou Ying (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2020)
Mathematics is one of the most important courses in junior high school. Students' attitude and engagement in mathematics learning will affect their good habits of mathematics learning, and further affect their mathematics academic performance. The method used in this research is quantitative regression method. In this study, 317 students from Guangxi Yulin No.3 junior high school were tested on their mathematical learning engagement, attitude and academic achievement. The relationship between students’ mathematical attitude and their mathematical academic achievement as well as the role of mathematical learning engagement are explored in this research. The results show that mathematics attitude has a positive and direct impact on students’ mathematics academic performance and mathematics learning engagement plays an important role in the relationship between mathematics attitude and academic performance as their intermediary role.